2014
DOI: 10.1371/journal.pmed.1001700
|View full text |Cite
|
Sign up to set email alerts
|

Hand Sanitiser Provision for Reducing Illness Absences in Primary School Children: A Cluster Randomised Trial

Abstract: In a cluster randomized trial, Patricia Priest and colleagues find that providing hand sanitizer along with hand hygiene education in primary school classrooms, compared with hand hygiene alone, does not reduce school absences. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
0
29
1
1
Order By: Relevance
“…Our results differed from these, probably because the strategy of the educational program was different (we reinforced handwashing education during the follow‐up, pupils washed their hands more frequently), the size of the sample was larger, and the tracking period of our study was longer (in other studies they have lasted under 12 weeks, not including peak periods for respiratory infections). No respiratory infection reduction was observed in randomized study by Priest . This is not the same as our study, because we only provided hand hygiene education and hand sanitizer in the EG.…”
Section: Discussioncontrasting
confidence: 56%
“…Our results differed from these, probably because the strategy of the educational program was different (we reinforced handwashing education during the follow‐up, pupils washed their hands more frequently), the size of the sample was larger, and the tracking period of our study was longer (in other studies they have lasted under 12 weeks, not including peak periods for respiratory infections). No respiratory infection reduction was observed in randomized study by Priest . This is not the same as our study, because we only provided hand hygiene education and hand sanitizer in the EG.…”
Section: Discussioncontrasting
confidence: 56%
“…Effective hand hygiene practice in community settings, has demonstrated a reduction of infections occurring in childcare [7][8][9][10], schools [2,[11][12][13], and in the home [14][15][16]. According to Aiello et.…”
Section: Introductionmentioning
confidence: 99%
“…A cluster-randomised controlled trial of a novel educational intervention to increase nutrition knowledge in 38 state primary school of Cambridgeshire, UK, comprising 2519 children in class 5 and 6 (aged 9–11 years) showed that the nutrition knowledge score was higher in intervention than in control schools [ 40 ]. In another cluster-randomised trial in New Zealand primary schools, the addition of hand sanitizers in classrooms compared with usual hand hygiene did not prevent disease of a severity sufficient to cause school absence [ 41 ]. Given the similar age group of children (grade level 7), we can compare our study with the Guangzhou, China, cluster-randomised trial on a school-based prevention programme on adolescent cigarette smoking, which had improved smoking-related knowledge but did not change students’ attitudes towards smoking [ 22 ].…”
Section: Discussionmentioning
confidence: 99%